Intelligent Energy Management Scheme for Home Area Networks Using Fair Emergency Demand Response Programs (FEDRP) - Muhammad, Ali; Hushairi, Zen; Faisal, Rahman (ENCON 2013, 2013)
Smart grid has opened the door for the customers and supplying agencies to fully involve in all aspects of advanced electrical network through demand response programs. Demand response programs are the layouts offered by the utilities for the public to agree on the policies and regulations for smooth power and energy supply. This work presents in very detail all aspects of modeling the home area networks in context with demand and response. It introduces a new idea of load reduction by providing the fairness concept to home area network clients through attractive package / incentives in form of money or free units for each specified amount of load reduction in peak or emergency hours. The data for testing the program is taken from local grid station on request. The graphical and numerical results have been elaborated at the end for explaining the Fair emergency demand response program.